Factors Affecting Job Fatigue In Informal Sector Workers : A Systematic Review - Hubaybah, Hubaybah; M Ichbat Fadli Azim; Budi Aswin; La Ode Reskiaddin; Ismi Nurwaqiah Ibnu (International Journal of Health Engineering and Technology, 2022)
Work fatigue is a problem that must be prioritized, work fatigue is the second contributor to the number of work accidents after traffic accidents. The high number of informal workers allows high accidents in the workplace.The purpose of this study is to discuss the factors that influence fatigue in informal sector workers. This research is a descriptive study with a systematic review method. The literature search strategy uses a prism flow chart, and inclusion and exclusion criteria. The databases used include: PubMed, DOAJ, Science Direct, Taylor and Francis, and Google Scholar. Of the 25 articles, all of them used cross-sectional research. The average type of informal work obtained from the 25 articles is labor. Overall, the journal articles obtained discuss the factors that affect work fatigue in informal sector workers. Age, nutritional status, workload were found to affect work fatigue in informal sector workers. Meanwhile, working period, working hours and work environment were not found to be related to the incidence of CTS in informal sector workers.